Distributive Justice With and Without Culture - William A. Jackson (Journal of Cultural Economy, 2015)
Academic treatments of distributive justice normally adopt a static approach centred on resource allocation among a set of individual agents. The resulting models, expressed in mathematical language, make no allowance for culture, as they never engage with the society's way of life or the moulding of individuals within society. This paper compares the static approach to distributive justice with a cultural one, arguing that a case for redistribution should rest upon its cultural effects in assisting well-being and social cohesion. Unless we recognise culture, we can have little understanding of why inequalities matter, where they come from, and how they might be reduced. Redistribution may be motivated by universal value judgements taken from external sources, but it also entails internal cultural changes that refashion social relations through cumulative causation. In practical terms, it has to penetrate beyond reallocating resource endowments to bring revised attitudes in a society less tolerant of unequal outcomes. Egalitarian reforms will flourish only if they generate and reflect an egalitarian culture.
Keywords: B50; D30; D63; I30; Z10; 330; culture; distributive justice; inequality; egalitarianism; cumulative causation; welfare state